Vinculin association with actin cytoskeleton is necessary for stiffness-dependent regulation of vinculin behavior - Omachi, Tomohiro (PLoS One, 2017)
The extracellular matrix (ECM) is a major regulator of cell behavior. Recent studies have indicated the importance of the physical properties of the ECM, including its stiffness, for cell migration and differentiation. Using actomyosin-generated forces, cells pull the ECM and sense stiffness via cell-ECM adhesion structures called focal adhesions (FAs). Vinculin, an actin-binding FA protein, has emerged as a major player in FA-mediated mechanotransduction. Although vinculin is important for sensing ECM stiffness, the role of vinculin binding to actin in the ECM stiffness-mediated regulation of vinculin behavior remains unknown. Here, we show that an actin binding-deficient mutation disrupts the ECM stiffness-dependent regulation of CSB (cytoskeleton stabilization buffer) resistance and the stable localization of vinculin. These results suggest that the vinculin-actin interaction participates in FA-mediated mechanotransduction.